2006
DOI: 10.1073/pnas.0511030103
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ERK pathway or protein synthesis during reexposure to drugs of abuse erases previously learned place preference

Abstract: Repeated association of drugs of abuse with context leads to long-lasting behavioral responses that reflect reward-controlled learning and participate in the establishment of addiction. Reactivation of consolidated memories is known to produce a reconsolidation process during which memories undergo a labile state. We investigated whether reexposure to drugs had similar effects. Cocaine administration activates extracellular signal-regulated kinase (ERK) in the striatum, and ERK activation is required for the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
279
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(299 citation statements)
references
References 51 publications
16
279
4
Order By: Relevance
“…Similarly, we observed no change in ERK signaling in the hippocampus or cingulate cortex at a 5 min time point, likely due to the fact that activation of ERK signaling by morphine in these areas peaks at 20 min post injection (Valjent et al, 2004). Other studies show that inhibition of ERK during place conditioning blocks cocaine CPP (Valjent et al, 2006a). ERK induction at the 5 min time point indicates that stimulation of ERK would occur during exposure to the training chamber during place conditioning.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Similarly, we observed no change in ERK signaling in the hippocampus or cingulate cortex at a 5 min time point, likely due to the fact that activation of ERK signaling by morphine in these areas peaks at 20 min post injection (Valjent et al, 2004). Other studies show that inhibition of ERK during place conditioning blocks cocaine CPP (Valjent et al, 2006a). ERK induction at the 5 min time point indicates that stimulation of ERK would occur during exposure to the training chamber during place conditioning.…”
Section: Discussionsupporting
confidence: 54%
“…A trend for slightly higher levels of ERK1/2 phosphorylation in GKO mice (WT-Mor vs KO-Mor: F(3, 19) ¼ 2.4; p ¼ 0.08) correlates with the tendency for these animals to show increased behavioral sensitivity to morphine. Together with studies showing that ERK activity is necessary for place preference (Girault et al, 2007;Salzmann et al, 2003;Valjent et al, 2001Valjent et al, , 2006aValjent et al, , b, 2004 and that galanin reduces morphine CPP (Zachariou et al, 1999), these data suggest that galanin might regulate morphine reward via regulation of ERK signaling in the VTA. It is also possible that ERK activity in the VTA regulates the ability of galanin to modulate morphineinduced locomotor activation.…”
Section: Neurochemical Changes Downstream Of Morphine Signalingsupporting
confidence: 53%
See 2 more Smart Citations
“…The inhibition of ERKs in the amygdala has been reported to block the formation of long-term fear memory (Schafe et al, 2000), memory reconsolidation (Duvarci et al, 2005), and extinction (Herry et al, 2006). Furthermore, Valjent et al (2006) have shown that inhibition of the ERK pathway prior to reexposure to cocaine-paired context blocked conditioned place preference on the following trial. Future studies will show whether inhibition of ERKs in the amygdala could also interfere with cue-induced alcohol seeking.…”
Section: Regulation Of C-fos Expression and C-jun Activation Induced mentioning
confidence: 99%